Impact of Government Expenditure on Economic Growth In Sub-Saharan Africa: A Validity of Wagner’s Law - Kolapo, Funsho; Bolanle, Azeez; Mokuolu, Joseph; Oluwaleye, Taiwo; Alabi, Kehinde (International Journal of Scientific Research and Management (IJSRM), 2021)
The study investigated the impact of government expenditure on economic growth with special inclination to testing the Wagner’s law in Sub Saharan Africa between 1986 and 2018. Adopting the Panel first generation tests as well as the Panel Auto Regressive Distributed Lag (ARDL) and Pairwise Causality techniques, it was revealed that government expenditure causes economic growth rendering the Wagner’s law is invalid in the Sub-Saharan region. Also, it was further discovered that capital and recurrent expenditure exert negative effect on economic growth while total expenditure has positive effect on economic growth in the region. Therefore, based on the negativity of capital and recurrent expenditure, it is recommended that capital and recurrent expenditure must be monitored effectively to ensure that its increase will not exert any negative effect on economic growth while stringent measures as well as checks and balances must be adopted to curb corruption in Sub-Saharan Africa to ensure that funds are used exclusively for their intended purposes especially those pertaining to capital projects.